(2x+6)(x-13)=0

Simple and best practice solution for (2x+6)(x-13)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+6)(x-13)=0 equation:



(2x+6)(x-13)=0
We multiply parentheses ..
(+2x^2-26x+6x-78)=0
We get rid of parentheses
2x^2-26x+6x-78=0
We add all the numbers together, and all the variables
2x^2-20x-78=0
a = 2; b = -20; c = -78;
Δ = b2-4ac
Δ = -202-4·2·(-78)
Δ = 1024
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1024}=32$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-20)-32}{2*2}=\frac{-12}{4} =-3 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-20)+32}{2*2}=\frac{52}{4} =13 $

See similar equations:

| 714=x+5x/100 | | -7+m=6(3m-4) | | x=7x-3(x+6)=-2 | | (d+6)(2d^2-d+7)=0 | | 70x25(450-x)=60(450) | | 5x+2+5=-18 | | x^2+7x-248=0 | | 16+11x=-2+5x | | 26-4s=-9 | | 3(t+4)=18. | | 9d-2d÷4=32 | | 12k-4=5 | | 2×(2x-5)=3x-1 | | 1.5c-27=57 | | 8y=7+9y | | -4=-5x-28 | | 5+4(m-2)=-30-5m | | -5-3x=-7x+15 | | -8=-4/5m | | 1/2x-2/7=1/4(3x+5) | | -3=6-4a-5 | | 2x+26=12-94 | | 8=3(x+2)-2(x+1) | | 3x=x/16 | | 4p+6p=-20 | | 12x+5=12x+7 | | 15x=(-12x) | | 8x-3=6x+@ | | 12x+15=15x+15 | | 800-40w=1000 | | |6x+3|=27 | | 9=4b+5b |

Equations solver categories